2012
DOI: 10.1016/j.jtcvs.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxyethyl starch on bleeding after cardiopulmonary bypass: A meta-analysis of randomized trials

Abstract: Hydroxyethyl starch increased blood loss, reoperation for bleeding, and blood product transfusion after cardiopulmonary bypass. There was no evidence that these risks could be mitigated by lower molecular weight and substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 147 publications
0
96
0
2
Order By: Relevance
“…(9,21) Regarding 4% succinylated gelatin (the colloid of use in this study), and being a colloid of low average molecular weight, there was a believe that it escapes the capillary pores faster than that of medium and high molecular weight can do, hence, less plasma expanding effect (23) , however several studies have described gelatins and starches as equal plasma expanders both in: animal models (24)(25)(26) and human. (20,27) Moreover, in their study, Dileep et al (21) have described an equal duration of plasma expansion of both 4% succinylated gelatin (gelofusine) and 6% hydroxyethyl starch (Voluven) attributing this to the fact that hydroxyethyl starch is eliminated by the cleavage action of the serum amylase, which increased four times after infusion of hydroxyethyl starch as reported by Wilkes et al (28) The PaCO2 levels in this study were maintained by ventilation therefore, base excess (BE) and PH changes reflected any change in the non-respiratory (i.e. metabolic) state.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…(9,21) Regarding 4% succinylated gelatin (the colloid of use in this study), and being a colloid of low average molecular weight, there was a believe that it escapes the capillary pores faster than that of medium and high molecular weight can do, hence, less plasma expanding effect (23) , however several studies have described gelatins and starches as equal plasma expanders both in: animal models (24)(25)(26) and human. (20,27) Moreover, in their study, Dileep et al (21) have described an equal duration of plasma expansion of both 4% succinylated gelatin (gelofusine) and 6% hydroxyethyl starch (Voluven) attributing this to the fact that hydroxyethyl starch is eliminated by the cleavage action of the serum amylase, which increased four times after infusion of hydroxyethyl starch as reported by Wilkes et al (28) The PaCO2 levels in this study were maintained by ventilation therefore, base excess (BE) and PH changes reflected any change in the non-respiratory (i.e. metabolic) state.…”
Section: Discussion:-mentioning
confidence: 99%
“…Results of many studies support an evidence-based recommendation for the avoidance or cautious use of HES solutions in patients undergoing surgery with CPB. (20) Studies showed that, chloride containing solutions produce hyperchloremia proportional to 1910 their chloride content which persists for at least 6 hours. (21) The use of newer preparations of balanced colloids results in less impairment of acid base status and is considered to be a promising strategy to avoid metabolic acidosis associated with colloids suspended in 0.9% saline.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Such storage is not restricted to critically ill patients, but widespread in both healthy volunteers and surgical patients (Bellmann, Feistritzer et al, 2012;Wiedermann and Joannidis, 2014). Secondly, the occurrence of HES-induced coagulopathy is well-established (Hartog, Reuter et al, 2011) and is likely to negatively affect clinical outcome at least in certain settings (Navickis, Haynes et al, 2012;Haase, Wetterslev et al, 2013;Rasmussen, Johansson et al, 2014). Thirdly, beneficial effects with HES beyond intermediate surrogate markers, such as fluid use, have not yet been demonstrated.…”
Section: S17mentioning
confidence: 99%
“…In response, HES with a GMW of 200 kD and a lower molar substitution of 0.5 was developed (10% PentaspanÒ, Bristol-Myers Squibb, Montreal, QC, Canada), allowing much quicker renal elimination, although a degree of platelet dysfunction and increased risk of bleeding has still been shown. 17,18 Subsequent development of HES with a GMW of 130 kD and a molar substitution of 0.4 was undertaken, but molecules with low molar substitution are rapidly cleaved enzymatically by amylase, resulting in a short intravascular volume effect. 16 Since the metabolism of HES also depends on the C2/C6 hydroxyethylation ratio, wherein the higher the ratio the slower the breakdown, HES 130/0.4 with a higher C2/C6 ratio ([ 8) was developed (VoluvenÒ 6%, Fresenius Kabi Deutschland GmbH, Bad Homburg, Germany), giving rise to a synthetic molecule with a longer intravascular presence but producing a significant decrease in tissue persistence.…”
mentioning
confidence: 99%
“…Aussi, un HES ayant un PM de 200 kD et un taux de substitution molaire de 0,5 a été développé (10 % PentaspanÒ, Bristol-Myers Squibb, Montréal, QC, Canada) permettant une élimination rénale beaucoup plus rapide, même si un certain niveau de dysfonction plaquettaire et un risque hémorragique accru était encore constaté. 17,18 Le développement ultérieur d'un HES ayant un PM de 130 kD et un taux de substitution molaire de 0,4 a été entrepris, mais les molécules ayant un faible taux de substitution molaire ont été rapidement scindées par l'amylase, n'entraînant qu'un effet de volume intravasculaire de courte durée. 16 Considérant que le métabolisme du HES dépend également du rapport d'hydroxyéthylation C2/C6 (plus le rapport est élevé, plus la dégradation de la molécule est lente), un HES 130/0,4 ayant un rapport C2/C6 plus élevé ([ 8) a été développé (VoluvenÒ 6%, Fresenius Kabi Deutschland GmbH, Bad Homburg, Allemagne); cela a donné naissance à une molécule synthétique présente plus longtemps dans le compartiment intravasculaire, mais persistant significativement moins longtemps dans les tissus.…”
unclassified